Next-generation sequencing-based genomic profiling of advanced soft tissue and bone sarcomas - Gündoğdu, Yasemin; Şenocak Taşçı, Elif; Özer, Leyla; Boynukara, Can; Çeçen, Recep; Mutlu, Arda Ulaş; Yıldız, İbrahim (Frontiers in Oncology, 2025)
BackgroundSarcomas are rare mesenchymal tumors classified into soft tissue (STS) and bone sarcomas. Despite advances in treatment, the 5-year survival rate for metastatic disease remains low. There is still limited evidence regarding the use of next-generation sequencing (NGS).AimTo identify targetable genomic alterations that may play a crucial role in sarcoma treatment where therapeutic options are limited.Study designMethods: We conducted a retrospective; multicenter analysis of 81 patients diagnosed with STS and bone sarcomas who underwent NGS at Acıbadem Health Group Hospitals to investigate their mutation profiles and explore potential targeted therapies.ResultsGenomic profiling using four different NGS kits identified a total of 223 genomic alterations across the cohort. Genomic alterations were detectable in 90.1% of patients, with the most common types being copy number amplifications (26.9%) and deletions (24.7%). In addition, actionable mutations were identified in 22.2% of patients, rendering them eligible for FDA-approved targeted therapies. The most common alterations were found in TP53 (38%), RB1 (22%), and CDKN2A (14%) genes. Among the 79 patients with available microsatellite status data, all were microsatellite stable.ConclusionThe high proportion of patients eligible for targeted therapies identified underscores the critical need to integrate NGS-derived genetic insights into clinical practice to improve survival rates and treatment outcomes through more tailored therapeutic approaches for each individual. NGS also led to a reclassification of diagnosis in four patients, demonstrating its utility not only in therapeutic decision-making but also as a powerful diagnostic tool.